2022
DOI: 10.18176/jiaci.0515
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis: A Decade of a Nationwide Allergy Society Registry

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 39 publications
6
12
0
Order By: Relevance
“… 1 No fatalities in children due to HEA have been reported in these paediatric publications. 1 , 4 , 7 , 10 , 13 , 14 , 15 In this study predominance of infants and males was observed in both trigger groups. Age distribution with predominance of infants 4 , 13 , 14 , 15 and males (from 51% to 68%) 1 , 4 , 7 , 10 , 13 , 14 , 15 up to school age was also reported in other studies.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“… 1 No fatalities in children due to HEA have been reported in these paediatric publications. 1 , 4 , 7 , 10 , 13 , 14 , 15 In this study predominance of infants and males was observed in both trigger groups. Age distribution with predominance of infants 4 , 13 , 14 , 15 and males (from 51% to 68%) 1 , 4 , 7 , 10 , 13 , 14 , 15 up to school age was also reported in other studies.…”
Section: Discussionsupporting
confidence: 55%
“…Although CM and HE are common food allergens worldwide, especially in the population of young children, 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 10 , 13 , 14 , 15 there are no publications directly comparing their phenotypes. Our aim was to evaluate similarities and differences between these trigger groups.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is recommended to prescribe an adrenaline autoinjector whenever a PEG allergy is confirmed (2,3,11,16). Education on when and how to use the autoinjector device must be provided (29,30), since there is an ongoing risk of accidental exposure, especially in patients with immediate SAR. In these patients, systemic mastocytosis or mast cell activation syndromes must be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Patient education is paramount. Patients must have an allergy warning card and a written emergency treatment plan, and should always carry with them an adrenaline autoinjector (Figure 2) (2,16,29,30). They also need to be taught to check product labels, and should have access to advice from the allergy department.…”
Section: Discussionmentioning
confidence: 99%
“…Single-blind placebo-controlled food challenge. The test provides more objective results compared to the previous one because the food is not served in its natural form, it is hidden in a capsule [46][47][48]. The control food (placebo) is chosen so that it is as similar as possible in taste, smell, and texture.…”
mentioning
confidence: 99%